Chemical Regeneration of Activated Carbon After Adsorption of Ni(II) Ions - Chong, Kian Wei; Cho, Kin Hau (Indonesian Scholar Society, 2023)
The chemical regeneration of activated carbon (AC) has recently received greater attention because it allows high-cost granular AC and AC fibers to be reused with less effort and energy. The chemical regeneration of activated carbon after Ni(II) ions adsorption was investigated in this study. Various desorbing solutions were used to recover adsorbed Ni(II) ions to AC. The concentration of the most effective desorbing solution was optimized. The adsorption efficiency of the regenerated AC using merely an acidic desorbing solution was reduced. Therefore, additional treatment after desorption using an acidic desorbing solution was carried out using sodium hydroxide solution. The optimum concentration of sodium hydroxide was determined. Using 3% HCl and H2SO4 as desorbing solutions, more than 80% of Ni(II) ions could be desorbed from AC. However, the readsorption efficiency of Ni(II) ions by AC was reduced to less than 50% after the first regeneration. By treating the regenerated AC from the acidic desorbing solution with 1 % NaOH, the efficiencies in the Ni(II) ions adsorption and desorption were fully recovered to almost 100%.